Are companies in Luleå not responding to negative reviews - and are consumers in Luleå reading the reviews? - Eriksson, Johan; Rudling, Axel (Luleå tekniska universitet, Institutionen för ekonomi, teknik, konst och samhälle, 2022)
People's engagements in social communities online have over recent years proven to be of great importance on others' opinions when purchasing products. Word-of-Mouth (WOM) has been around since ancient times and is a concept about consumers communicating with each other about their experience about services and products. Over the last decades research on Word-of-Mouth has increased when it was discovered how it has the power to influence consumers' purchase behaviours. The modern era of the introduction of the internet gave Word-of-Mouth a new concept called Electronic Word-of-Mouth (eWOM) that has given people the opportunity to share their negative and positive experiences online with others by leaving reviews. These reviews can be read by customers with access to the internet and could change their purchase intentions and therefore affect the company's sales and reputation. It has given the companies the opportunity to read about customers reviews and the chance to respond to the reviews by leaving comments online. This gave this study the opportunity to research if companies in Luleå are responding to negative reviews. As well, if the customers believe that their purchase intention is being affected by other users' reviews, and if the customers believe the companies can change the outcome of a review by responding to them. In this study, quantitative research was used to collect data through surveys in Facebook groups with questions limited to Luleå. The questions were divided into three sections: Reading reviews, Responding to reviews, and Purchase intention. The study found that there was a relationship between the variables reading reviews, responding to reviews, and purchase intention. Previous literature has meant that people write more negative reviews when they have the ability to complain and write reviews through the Internet. However, for this study in Luleå, it was shown that this is not the case. It was found that few of the respondents gave negative reviews about the businesses in Luleå and that ...